Beta Convergence and Sigma Convergence: Evidence from Indonesian District-Level Data - Nenny Hendajany; Didin Saepudin; Ae Suaesih (Universitas Udayana, 2017)
In this paper, we describe three things, (1) Evidence of Beta-convergence’s existence in Indonesian districts-level data, (2) the reason of why Sigma-convergence may not accompany Beta-convergence, and (3) the demonstration to show that Sigma-convergence cannot be detected at the districts level across Indonesia using Indonesian districts -level data that contains over 277 cross-sectional observations. If Indonesian individual provinces are considered separately, we find only 2 out of 25 provinces with detected Sigma-convergence. But also, in many cases statistically significant Sigma-divergence is found.